Multicentre cluster randomised trial comparing a community group exercise programme with home based exercise with usual care for people aged 65 and over in primary care - Iliffe, Steve; Kendrick, Denise; Morris, Richard; Masud, Tahir; Gage, Heather; Skelton, Dawn; Dinan, Susie; Bowling, Ann; Griffin, Mark; Haworth, Deborah; Swanwick, Glen; Carpenter, Hannah; et al. (NIHR Health Technology Assessment Programme, 2014)
Background: Regular physical activity (PA) reduces the risk of falls and hip fractures, and mortality from all causes. However, PA levels are low in the older population and previous intervention studies have demonstrated only modest, short-term improvements.